The Effect of Security Risks on Interest in Using The Quick Response Code Indonesian Standard (QRIS) Among FKIP UNS Students with Ease of Use as an Intervening Variable - Laely Fatonah; Dewi Kusuma Wardani (Universitas Negeri Surabaya, 2026)
Objective: This study aims to analyze the effect of security risks on the interest in using QRIS through ease of use as an intervening variable. Method: This study uses a quantitative method with a sample of 384 FKIP UNS students determined by purposive sampling technique. Variable measurement uses a 4-point Likert scale processed using SPSS 28 software. Results: The study shows that security risks have a significant effect on the ease of use of QRIS (β = -0.625; p < 0.001), security risks have a significant effect on the interest in using QRIS (β = -0.070; p < 0.011), ease of use has a significant effect on the interest in using QRIS (β = 0.863; p < 0.001), security risks have a significant effect on the interest in using QRIS mediated by ease of use (t = -14.374; p < 0.001). Novelty: This study combines security risk as a factor influencing interest in using QRIS with ease of use as an intervening variable as an extension of the research to determine the extent of its influence.